A study of face detection algorithm - Ye, Htun Aung. (2012)
This paper conducts a study of a most well-known face detection algorithm available to computer vision community. The existing code written in C+ language is downloaded as the study platform which is based on simple feature-based and Adaboost-based face detection system and the algorithm with some modifications initiated for studying various difficult cases on face detection. Some step by step improvements of simulation results and discussions of problems encountered and future works will be provided.